The Effect of Greenwashing Perceptions on Green Product Purchasing Decisions: a Case Study on Bottled Drinking Water Consumers - Kusnianti, Sri Libri; Sofilda, Eleonora; Santosa , Budi (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
As global awareness of sustainability continues to rise, greenwashing remains a significant obstacle that weakens the credibility of companies' environmental claims. While many businesses have adopted green marketing to support sustainability objectives, deceptive or exaggerated claims still undermine consumer trust and hinder the shift toward responsible consumption. This study aims to analyze the influence of greenwashing perception on the decision to buy green products, by highlighting the mediating role of feelings of betrayal as well as the moderation of environmental responsibility and consumer environmental knowledge. A quantitative approach was used in this study with a cross-sectional design. Data was collected from 300 respondents who consume plastic bottled drinking water in Jakarta using purposive sampling techniques. Data analysis was carried out using the Structural Equation Modeling (SEM) method. The findings reveal that perceptions of greenwashing significantly and negatively affect green purchasing decisions, primarily through the emotional response of perceived betrayal. This feeling serves as a key mediator, decreasing consumers’ willingness to support products seen as insincere in their sustainability messaging. Interestingly, environmental responsibility and knowledge did not moderate this effect.  These results contribute to SDG 12 (Responsible Consumption and Production), and support SDG 13 (Climate Action) by highlighting the importance of honest and transparent sustainability communication. For the bottled water industry, maintaining consistency and transparency between environmental claims and actual practices is essential to earning consumer trust and promoting sustainable consumption